PENINGKATAN KEMAMPUAN INTERAKSI SOSIAL PADA ANAK USIA DINI MELALUI KEGIATAN BERMAIN BALOK SECARA BERKELOMPOK DI TKN PEMBINA 1 PALEMBANG - Jauza Zanety, Mahsya; Sumarni, Sri; Ratiyah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2023)
Social interaction skills certainly have an important role in early childhood because in carrying out interactions children will be taught how to be able to live in society in their environment. So that the development of social interaction skills needs to be supported by the family environment and the school environment. However, in the current era where technology has developed very rapidly, it has affected children's development. So the need for block play activities to be able to develop children's social interactions. The purpose of this study was to describe how group play with blocks can improve children's social interaction skills. This research is a study using a class action design. This classroom action research was conducted at Pembina 1 Palembang State Kindergarten in class B4 which has 15 children. The design chosen is a cycle model that is carried out repeatedly and continuously. From the data in cycle I which showed a result of 62% and experienced an increase in cycle II with a percentage of 79.33% this shows that it is in the criteria of Good Development. So it was concluded that playing blocks in groups improves children's interaction skills.